Assessment of early kidney injury caused by asymptomatic bacteriuria in children with type 1 diabetes - Gihan M. Bebars; Asmaa N. Mostafa; Hend M. Moness; Reem A. Abdel Aziz (BMC Pediatrics, 2022)
Abstract Introduction Infection is one of the most frequent causes of morbidity and mortality in diabetic patients. Some microorganisms become more virulent in a high glucose concentration. Diabetics are more likely to have asymptomatic and symptomatic bacteriuria. NGAL is secreted in high concentrations into the blood and urine within two hours of AKI. Objectives The aim of the study is early detection of UTI in type1diabetic children through screening of their urine samples, and measurement of NGAL urinary levels in cases with asymptomatic bacteriuria for early detection of AKI to prevent serious complications. Patients and methods One thousand twenty-two known diabetic children on regular follow up in endocrine outpatient clinic at Minia Children University hospital were screened for UTI. From them only 52 diabetic children were diagnosed as asymptomatic bacteriuria (group I), 52 diabetic children with normal urine analysis (group II) and 52 apparently healthy children, age and sex matched, served as controls (group III). CBC, Renal function test, HbA1c, hs- CRP, Albumin/creatinine ratio, urine examination, urine culture, GFR and urinary NGAL were done to all children. Results Thirty-seven females (71.2%) had asymptomatic bacteriuria, Hs CRP and urinary NGAL were significantly higher, while GFR was significantly lower in diabetic children with bacteriuria than the other two groups. For diabetic children with bacteriuria, (AUC) for NGAL was 1 with optimal cutoff value of > 44.1 (Sensitivity 100% and Specificity 100%) while AUC for hsCRP was 0.887 with optimal cutoff value of > 1 (Sensitivity 82.69% and Specificity 90.38%). Conclusion Routine urine analysis should be done for all diabetic children even if they are asymptomatic. NGAL and hsCRP are non-invasive methods that could detect early renal injury in these patients thus, early, and proper management of UTI should be started to prevent renal injury.